Collaborative Governance dalam Pengelolaan Ruang Terbuka Hijau di Kota Makassar - Nur Asyifa T; Andi Aslinda; Herman H (Universitas Negeri Makassar, 2025)
This research investigates collaborative governance in the management of Green Open Space (RTH) in Makassar City, with a particular focus on Ujung Pandang District. The study aims to analyze the dynamics of collaborative governance, identifying both supporting and inhibiting factors that influence the effective management of RTH. Employing a qualitative approach with descriptive methods, data collection was conducted through a combination of observation, interviews, and documentation to gather comprehensive insights into the governance processes. The data analysis technique utilized in this research is interactive data analysis, which involves stages of data condensation, presentation, and conclusion drawing. The findings reveal that collaborative governance in managing Green Open Space in Makassar City has been largely effective, although certain shortcomings and challenges persist. Key aspects of the collaboration include: 1) Collaboration Dynamics: The inclusive partnership among the Makassar city government, PT Kalla Group, and the Ujung Pandang community has been instrumental in ensuring sustainable management of RTH. 2) Collaborative Actions: The implementation of Makassar Mayor Regulation No. 71 of 2019 has facilitated initiatives for planning and maintaining RTH, fostering stakeholder cooperation. PT Kalla Group plays a crucial role by funding and developing RTH, while the community is actively involved in maintenance and supervision. 3) Impact and Adaptation: This collaboration has led to significant improvements in both the quality and quantity of RTH, promoting stronger partnerships among stakeholders and enhancing community engagement. Despite these positive outcomes, challenges such as limited human resources remain significant obstacles to effective governance. Supporting factors include clearly defined collaborative roles, established RTH management policies, and financial commitments from the private sector. Conversely, the main inhibiting factors are ineffective coordination among parties and low levels of active community participation. Addressing these challenges is essential for enhancing the effectiveness of collaborative governance in managing Green Open Space in Makassar City, ultimately contributing to a more sustainable urban environment and improved quality of life for residents.